Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

Leuconostoc mesenteroides TH-ST373 Cell-Free Supernatant Against Multidrug-Resistant Escherichia coli - Gyeong-Seon Yi; Thi Minh Nguyen Trang; Jae-Woo Kim; Jin-woo Choi; Ye-Rim Choi; So-Hee Chun; Qiwen Zheng; Tae-Hoo Yi (Probiotics and Antimicrobial Proteins, 2026)

Reassembled yeast vacuoles preserve endothelial viability and barrier integrity in an in vitro blood–brain barrier model - Yoon-Young Hwang; Cho-Im Oh; Jin-Pyo Lee; Su-Min Lee; Dae-Young Park; In-Hwan Oh; Tae-rim Kim; Ok Chan Jeong; Ji-Young Ahn; Yang-Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2026)

Risk assessment of benzophenone-3, a UV filter in cosmetics - Kyu-Tae Kang; Minhyuk Kim; Chi Rim Sung; Jung Dae Lee; Taehyung Yoon; Kyu-Bong Kim; Seung Jun Kwack; Joo Young Lee (Toxicological Research, 2026)

Development of a neutralization ccombody, synthetic hagfish antibody, for viral hemorrhagic septicemia virus (VHSV) targeting glycoprotein G - Abigail Joy D. Rodelas-Angelia; Mark Rickard N. Angelia; Seung Pyo Jeong; Young Rim Kim; Myoung Gwang Choi; Hyoung Jun Kim; Se Ryun Kwon; Kim D. Thompson; Tae Sung Jung (Fish & Shellfish Immunology, 2026)

Lignin-tailored lignocellulose nanofiber films for light management using a deep eutectic solvent - Youngho Jeon; Kangyun Lee; Yuri Seo; Joonhoo Jung; Suji Lee; Seohyun Park; Hyeonjin Rim; Dongryul Kim; Jung Tae Lee; Jungmok You (Chemical Engineering Journal, 2025)

Systemic toxicity and toxicokinetics study of self-assembled-micelle inhibitory RNA-targeting amphiregulin in cynomolgus monkeys following intravenous injection - Hyeon-Young Kim; Tae-Rim Kim; Sung-Hwan Kim; In-Hyeon Kim; Woong-Il Kim; Jun-Hong Park; Youngho Ko; Sungil Yun; Han-Oh Park; Jong-Choon Kim (Toxicological Research, 2025)

Development of a Maritime Transport Emulator to Mitigate Data Loss from Shipborne IoT Sensors - Chae-Rim Park; Do-Myeong Park; Tae-Hoon Kim; Byung O Kang; Byung-Kwon Park (Journal of Marine Science and Engineering, 2025)
Recently, the maritime logistics industry has been transitioning to smart logistics by leveraging such technologies as AI and IoT. In particular, maritime big data plays a significant role in providing various services, including ship operation monitoring and greenhouse gas emissions assessment, and is considered essential for delivering maritime logistics services. Marine big data comprise real-world data collected during ship operations, but it is susceptible to loss due to temporal and environmental constraints. To address this issue, an Emulator is proposed to generate supplemental data, including location data, data count, and average distance, using accumulated maritime transport data. This study proposes an Emulator that repetitively generates new data such as location data, data count, and average distance using maritime transport data accumulated up to now. The location data is generated using the cumulative distance and trigonometric ratios based on the location information of standard routes. The data count and average distance are calculated based on user-input parameters such as voyage time and data interval. The generated data is inserted into a database and monitored on a map in real time. Experiments were conducted using maritime transport route data, and the results validated the effectiveness of the Emulator.

Al2O3-sheathed Si/Li2SiO3 nanocomposite anode materials for high-performance lithium-ion batteries - Donghan Youn; Ji Young Kim; Tae Rim Lee; Jiyoung Han; Sungjin Kim; Hansu Kim (Chemical Engineering Journal, 2025)

Maximizing clean hydrogen release from perhydro-benzyltoluene: Energy-efficient scale-up strategies and techno-economic analyses - In Seop Lim; Yoonseong Jeong; Yeonsu Kwak; Eui-Rim On; Quan Nguyen Dao; Hyangsoo Jeong; Hyuntae Sohn; Suk Woo Nam; Tae-Hoon Lim; Karsten Müller; Yongmin Kim (Chemical Engineering Journal, 2023)

Exploring the potential hypothalamic role in mediating cisplatin-induced negative energy balance - Yang Tae Kim; Byong Seo Park; Hye Rim Yang; Seon Yi; Il Seong Nam-Goong; Jae Geun Kim (Chemico-Biological Interactions, 2023)

Macroalgae as a source of sugar and detoxifier biochar for polyhydroxyalkanoates production by Halomonas sp. YLGW01 under the unsterile condition - Shashi Kant Bhatia; Jeong Hyeon Hwang; Suk Jin Oh; Hyun Jin Kim; Nara Shin; Tae-Rim Choi; Hyun-Joong Kim; Jong-Min Jeon; Jeong-Jun Yoon; Yung-Hun Yang (Bioresource Technology, 2023)

Algal biochar mediated detoxification of plant biomass hydrolysate: Mechanism study and valorization into polyhydroxyalkanoates - Shashi Kant Bhatia; Ranjit Gurav; Do-Hyun Cho; Byungchan Kim; Hee Ju Jung; Su Hyun Kim; Tae-Rim Choi; Hyun-Joong Kim; Yung-Hun Yang (Bioresource Technology, 2023)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.

Summer climate variability over Korea in association with diverse features of ENSO evolution - Sae-Rim Yeo; Seon Tae Kim (Climate Dynamics, 2021)

Genotypic Variation in Fatty Acids in Whole Grain Sesame (Fatty Acids in Whole Grain Sesame) - Qiang He; Tae-Rim Lee; Jie Yu; Win Htet Oo; Min-Young Yoon; Myeong-Hyeon Min; Sang-Ho Chu; Kyu-Won Kim; Young-Sang Lee; Yong-Jin Park (Journal of Crop Science and Biotechnology, 2020)

Calibration of the Pyranometer Sensitivity Using the Integrating Sphere - Bu-Yo Kim; Kyu-Tae Lee; Il-Sung Zo; Sang-Ho Lee; Hyun-Seok Jung; Se-Hun Rim; Jeong-Pil Jang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Correction to: Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Effects of Angelica gigas extract on the oral pharmacokinetics of gefitinib in rats - Hye-Rim Kim; Jong-Woo Jeong; Sang Hoon Joo; Tae-Sung Koo (Journal of Pharmaceutical Investigation, 2018)

Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Retrieval Algorithm for Broadband Albedo at the Top of the Atmosphere - Sang-Ho Lee; Kyu-Tae Lee; Bu-Yo Kim; ll-Sung Zo; Hyun-Seok Jung; Se-Hun Rim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Phototoxicity Evaluation of Pharmaceutical Substances with a Reactive Oxygen Species Assay Using Ultraviolet A - Yong Sun Lee; Jung-Sun Yi; Hye Rim Lim; Tae Sung Kim; Il Young Ahn; Kyungyuk Ko; JooHwan Kim; Hye-Kyung Park; Soo Jung Sohn; Jong Kwon Lee (Toxicological Research, 2017)

Anti-inflammatory effects of fimasartan via Akt, ERK, and NFκB pathways on astrocytes stimulated by hemolysate - Xiu-Li Yang; Chi Kyung Kim; Tae Jung Kim; Jing Sun; Doeun Rim; Young-Ju Kim; Sang-Bae Ko; Hyunduk Jang; Byung-Woo Yoon (Inflammation Research, 2016)

The Arabidopsis PLAT domain protein1 promotes abiotic stress tolerance and growth in tobacco - Tae Kyung Hyun; Alfonso Albacete; Eric van der Graaff; Seung Hee Eom; Dominik K. Großkinsky; Hannah Böhm; Ursula Janschek; Yeonggil Rim; Walid Wahid Ali; Soo Young Kim; Thomas Roitsch (Transgenic Research, 2015)

RNA-seq analysis of Rubus idaeus cv. Nova: transcriptome sequencing and de novo assembly for subsequent functional genomics approaches - Tae Kyung Hyun; Sarah Lee; Dhinesh Kumar; Yeonggil Rim; Ritesh Kumar; Sang Yeol Lee; Choong Hwan Lee; Jae-Yean Kim (Plant Cell Reports, 2014)

Genome-wide and molecular evolution analyses of the KT/HAK/KUP family in tomato (Solanum lycopersicum L.) - Tae Kyung Hyun; Yeonggil Rim; Ekyune Kim; Ju-Sung Kim (Genes & Genomics, 2014)

De novo transcriptome sequencing of Momordica cochinchinensis to identify genes involved in the carotenoid biosynthesis - Tae Kyung Hyun; Yeonggil Rim; Hui-Jeong Jang; Cheol Hong Kim; Jongsun Park; Ritesh Kumar; Sunghoon Lee; Byung Chul Kim; Jong Bhak; Binh Nguyen-Quoc; Seon-Won Kim; Sang Yeol Lee; et al. (Plant Molecular Biology, 2012)

Cell-to-cell trafficking of RNA and RNA silencing through plasmodesmata - Tae Kyung Hyun; Mohammad Nazim Uddin; Yeonggil Rim; Jae-Yean Kim (Protoplasma, 2011)

2-Ketogluconic Acid Production and Phosphate Solubilization by Enterobacter intermedium - Kil Yong Kim; Hoon Hwangbo; Ro Dong Park; Yong Woong Kim; Yo Sup Rim; Keun Hyung Park; Tae Hwan Kim; Jang Sun Suh (Current Microbiology, 2003)